2019
DOI: 10.12659/msm.915649
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Monolayers on Hyaluronic Acid Membranes as “Upside-Down” Grafts Reconstitute Full-Thickness Wounds

Abstract: BackgroundSkin replacement by means of cultured epithelial keratinocytes is a well-accepted method. However, several clinical drawbacks of sheet autografts (CEA – cultured epithelial autografts) have stimulated various efforts to optimize cell culture and cell delivery. Recent developments include use of cell monolayers instead of a fully differentiated epithelium, as well as use of various biomaterials to grow and transport the cultured cells.To optimize the transfer of human keratinocytes directly to the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Compared to the above methods, CST has significant advantages, which can resolve the above- mentioned drawbacks [ 45 , 46 ]. In the wound healing, mono-layer cell sheet or three-layer cell sheet is used to repair the wound healing [ 45 , 47 ]. Although a relatively high wound healing rate can be obtained, still a lot of improvement can be made.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the above methods, CST has significant advantages, which can resolve the above- mentioned drawbacks [ 45 , 46 ]. In the wound healing, mono-layer cell sheet or three-layer cell sheet is used to repair the wound healing [ 45 , 47 ]. Although a relatively high wound healing rate can be obtained, still a lot of improvement can be made.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Horch et al 40 studied in vivo the use of keratinocyte monolayers in hyaluronic acid membranes demonstrating that when keratinocytes were directly implanted towards the full-thickness wound bed of athymic mice, formation of a multilayered and differentiating epidermis was faster (14 days) than conventional technique (>21 days).…”
Section: Human Adult Skin Cells In Tesssmentioning
confidence: 99%
“…There have been numerous reports on these acellular skin substitutes being used as scaffolds in conjunction with the sheet form of CEA for complex wounds. 7,[12][13][14][15] Matsumura et al 16 reported the successful use of combined CEA and acellular skin substitution in severe burn patients.…”
Section: Original Article Smjmentioning
confidence: 99%